Cyclic Formation Stability of 1,1,1,2-Tetrafluoroethane Hydrate in Different SDS Solution Systems and Dissociation Characteristics Using Thermal Stimulation Combined with Depressurization - Cheng, Chuanxiao; Wang, Fan; Zhang, Jun; Qi, Tian; Jin, Tingxiang; Zhao, Jiafei; Zheng, Jili; Li, Lingjuan; Li, Lun; Yang, Penglin; Lv, Shuai (ACS omega, 2019)
Cold storage using hydrates for cooling is a high-efficiency technology. However, this technology suffers from problems such as the stochastic nature of hydrate nucleation, cyclic hydrate formation instability, and a low cold discharge rate. To solve these problems, it is necessary to further clarify the characteristics of hydrate formation and dissociation in different systems. First, a comparative experimental study in pure water and sodium dodecyl sulfate (SDS) solution systems was conducted to explore the influence of SDS on the morphology of the hydrate and the time needed for its formation under visualization conditions. Subsequently, the cyclic hydrate formation stability was investigated at different test temperatures with two types of SDS solution systemswith or without a porous medium. The induction time, full time, and energy consumption time ratio of the first hydrate formation process and the cyclic hydrate reformation process were analyzed. Finally, thermal stimulation combined with depressurization was used to intensify hydrate dissociation compared with single thermal stimulation. The results showed that the growth morphology of hydrate and the time required for its formation in the SDS solution system were obviously different than those in pure water. In addition, the calculation and comparison results revealed that the induction time and full time of cyclic hydrate reformation were shorter and the energy consumption time ratio was smaller in the porous medium. The results indicated that a porous medium could improve the cyclic hydrate formation process by making it more stable and by decreasing time and energy costs. Thermal stimulation combined with depressurization at different backpressures (0.1, 0.2, 0.3, and 0.4 MPa) effectively promoted the decomposition of hydrates, and with the decrease in backpressure, the dissociation time decreased gradually. At a backpressure of 0.1 MPa, the dissociation time was reduced by 150 min. The experimental results presented the formation and dissociation characteristics of 1,1,1,2-tetrafluoroethane hydrates in different systems, which could accelerate the application of gas hydrates in cold storage.